Penataran dan Pelatihan Wasit Bulu Tangkis Tingkat Kabupaten / Kota Se-Provinsi Riau Pbsi Kabupaten Kampar Dan Universitas Pahlawan - Jufrianis Jufrianis; Vigi Indah Permatha Sari; Herli Pardilla (Joska: Jurnal Isori Kampar, 2024)
Badminton is a sport that is very popular with Indonesian people. With so many people playing badminton, badminton has become one of the favorite sports of Indonesian people. Refereeing as part of badminton coaching is very important. When the referee enforces the rules of the game, the referee's role becomes the determining factor. A professional referee can be neutral and enforce the applicable rules of the game. Apart from that, there are also other criteria that are also needed so that a badminton referee must be physically and mentally healthy. The mechanism for implementing activities in general is in the form of planning/preparation, implementation, observation and evaluation, and reflection. This activity took place on 25 July –26 July 2024, a theoretical presentation in the Hero University hall and continued on 27 July –28 July 2024, a referee practice exam at the Muara Uwai Bangkinang Seberang Badminton Gym. It is hoped that this activity can produce competent and professional badminton referees in Riau Province